Micro Financing in MSMES Development at BRI Syariah KCP Palopo (Study of The Implementation of Murabahah Contracts) - Ria Masita Tuljanna (Program Studi Perbankan Syariah, IAIN Palopo, 2021)
This study aims: To determine the application of the murabaha contract system to microfinance at BRI Syariah KCP Palopo; This type of research is field research using qualitative research methods. The data analysis technique used is descriptive analysis and SWOT analysis is measured by interviews to determine the overall internal and external factors of microfinance at BRI Syariah KCP Palopo. The results of research in the field show that 1) The application of the murabaha contract system in microfinance at BRI Syariah performs one contract first, the first is done with a wakalah contract, then continues with a murabaha contract. 2) Provision of microfinance using a murabaha contract has an influence on MSME business development in terms of business capital, turnover, income, number of products and expansion of the location of the business. 3) In the process of providing microfinance to MSME customers, BRI Syariah experienced obstacles such as a lack of understanding by customers about contracts and products, and the ineffectiveness of using business capital. From the results of the SWOT analysis based on the identification of internal factors and external factors on Micro Financing Products at BRI Syariah KCP Palopo, namely creating strategies to overcome weaknesses and threats and increase strengths and opportunities, one of which is BRI Syariah introducing sharia bank products to MSMEs to increasing interest in taking financing at BRI Syariah KCP Palopo.